2010
DOI: 10.1002/qua.22699
|View full text |Cite
|
Sign up to set email alerts
|

MRCI investigations on dissociation energy and molecular constants of BCl(X1Σ+) radical

Abstract: ABSTRACT:The equilibrium internuclear separations and harmonic frequencies of the BCl(X 1 R þ ) radical have been studied using the highly accurate valence internally contracted multireference configuration interaction (MRCI) approach in combination with a series of correlation-consistent basis sets in the valence range. To accurately determine the ground-state dissociation energy of the radical, the potential energy curve (PEC) is calculated at each basis set over the internuclear distance range from about 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The overall comparison of the present results with experiment and those of Ref. at the MRCI+scalar relativity (DK2)/aug‐cc‐pV5Z level shows that scalar relativistic effects are unimportant, whereas small deviations from experiment are due to missing core (1s 2 / B 1s 2 2s 2 2p 6 / Cl ) correlation effects. It is of interest, however, to notice the following: (a) the electric dipole moment µ reported here for the first time and unknown experimentally is 1.34–1.35 D, obtained either as an expectation value < µ > or using the finite field approach, µ ff .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The overall comparison of the present results with experiment and those of Ref. at the MRCI+scalar relativity (DK2)/aug‐cc‐pV5Z level shows that scalar relativistic effects are unimportant, whereas small deviations from experiment are due to missing core (1s 2 / B 1s 2 2s 2 2p 6 / Cl ) correlation effects. It is of interest, however, to notice the following: (a) the electric dipole moment µ reported here for the first time and unknown experimentally is 1.34–1.35 D, obtained either as an expectation value < µ > or using the finite field approach, µ ff .…”
Section: Resultssupporting
confidence: 61%
“…The first part of Table collects CC and MRCI(+Q)/A6ζ spectroscopic parameters of BCl( X 1 Σ + ) along with experimental and theoretical results from Ref. . The overall comparison of the present results with experiment and those of Ref.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…18 This was a MRCI study using the AV5Z basis set of Dunning and co-workers on both atoms. 38,39 The same basis set was used in a recent calculation of the X 1 S + state 40 that concentrated on the vibrational levels of the radical. A (1 + 1) Resonance Enhanced Multiphoton Ionisation (REMPI) study by Zhu et al 41 reported spectroscopic constants for the spin-forbidden transition b 3 S À ' X 1 S + and C 1 S + ' X 1 S + .…”
Section: Previous Work (A) Alh Radicalmentioning
confidence: 99%
“…Then Equation ( 2) can be solved by LEVEL [26] to obtain E ab inito ν . The corresponding experimental data are collected [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], and used to construct offset data set. There are hundreds of records here, the first few rows are listed in Table 1.…”
Section: Obtain Offset Data Setmentioning
confidence: 99%